2020
DOI: 10.1007/s42399-020-00651-z
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography Perfusion Core Infarct Measurement Compared to Diffusion-Weighted Magnetic Resonance Imaging in Patients with Revascularization of Anterior Circulation, Large Artery Occlusion Ischemic Stroke

Abstract: Relative cerebral blood flow (CBF) < 30% has been identified as a predictor of infarct core on computed tomography perfusion (CTP). We investigated the relationship between CTP-predicted infarct core and diffusion-weighted imaging magnetic resonance imaging (DWI MRI). We conducted a retrospective analysis comparing infarct core (CBF < 30%; RAPID iSchemaView) and post-revascularization DWI MRI (ADC < 620 cc; RAPID iSchemaView) in patients with internal carotid artery (ICA) or proximal middle cerebral artery (MC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…A search of the references of included studies and previous systematic reviews [17, 18, 20, 21] identified 4 additional studies. A total of 167 full-text papers were reviewed and 48 studies [8, 12‒14, 29‒72] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…A search of the references of included studies and previous systematic reviews [17, 18, 20, 21] identified 4 additional studies. A total of 167 full-text papers were reviewed and 48 studies [8, 12‒14, 29‒72] met the inclusion criteria (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical and radiological outcome data from our network have been published. [11][12][13][14][15][16][17] We collected data 6 months (November 2020 to April 2021) before implementing the new workflow described hereinafter and 6 months after (May 2021 to October 2021). We included all adult patients with suspected stroke symptoms presenting to one of our stroke network's nonthrombectomy facilities within 4.5 to 24 hours of LKW.…”
Section: Methodsmentioning
confidence: 99%
“…Our system includes 2 Joint Commission–certified thrombectomy centers: one is a comprehensive stroke center, and the other is thrombectomy capable certified. Clinical and radiological outcome data from our network have been published 11–17. We collected data 6 months (November 2020 to April 2021) before implementing the new workflow described hereinafter and 6 months after (May 2021 to October 2021).…”
Section: Methodsmentioning
confidence: 99%